Performance Evaluation of Fixed Crane Operations Using Overall Equipment Effectiveness Method in Port Container Handling Activities - Riana, Riska Iva; Fauziah (PT. SAFARI AMALIA, 2025)
Efficient container handling is crucial to maintaining productivity and competitiveness in port operations. This study evaluates the performance of fixed crane equipment using the Overall Equipment Effectiveness (OEE) method to identify factors contributing to productivity loss. Data were collected through observation, interviews, and operational records, focusing on loading time, downtime, operation time, processed amount, and defect rate. The analysis assessed three OEE indicators: availability, performance efficiency, and quality rate. Results revealed that crane availability ranged from 84–86%, performance efficiency from 14–21%, and quality rate remained at 100%. The overall OEE value of 12–18% was significantly below the world-class standard of 85%, indicating low operational efficiency. The primary causes of reduced effectiveness included operator negligence, overloading, and insufficient radiator maintenance. To enhance reliability, the study suggests introducing a 200-hour preventive maintenance schedule emphasizing radiator inspection, operator training, and strict load monitoring. The research demonstrates that applying the OEE framework allows port managers to quantify equipment performance, identify major loss sources, and implement targeted strategies to reduce downtime and improve throughput in container handling operations